Need for a pedagogy of large groups in Congo -Kinshasa (International Journal of Scientific Research and Management (IJSRM), 2022)
This article starts from a constant according to which the classes of Kinshasa have become bloated because of the mismatch between the rhythm of the evolution of the school demand and the capacity of reception and possibility of supervision. An inadequacy justified by the state of the economies, especially the budgets allocated to education in the countries located south of the Sahara in which the Democratic Republic of Congo is located. In order to solve this large group problem in classrooms, a purely pedagogical solution is proposed in this work. This is group pedagogy. Teachers should therefore be trained in the pedagogy of large groups during retraining to enable them to take charge of these classes.